Performance assessment of CO2 supermarket refrigeration system in different climate zones of China. (15th March 2020) - Sun, Zhili; Li, Jiamei; Liang, Youcai; Sun, Huan; Liu, Shengchun; Yang, Lijie; Wang, Caiyun; Dai, Baomin
Highlights: A comprehensive performance of R134a-TCS, R744-TCS and R744-PC-TCS is compared. Five typical representative cities are selective to represent five major climate zones in China. The seasonal performance of three systems in different climates is analyzed. The proposed R744-PC-TCS has a great potential for the supermarket refrigeration application. Abstract: In this paper, a R744 Partial Cascaded Two-stage Compression Refrigeration System (R744-PC-TCS) was proposed and evaluated in terms of coefficient of performance (COP) and seasonal energy efficiency ratio (SEER) when it operated in five typical climate representative cities in China. R134a and CO2 are used as refrigerants in this study. The results show that the SEER of the supermarket refrigeration system in the severe cold zone and the mild zone is higher than that of the other climate zones. The performance of the R134a Two-stage Compression Refrigeration System (R134a-TCS) performs better than the R744 Two-stage Compression Refrigeration System (R744-TCS). However, both COP and SEER of the CO2 system can be improved significantly by adding a parallel compressor, as well as using the single-stage vapor compression partial cascade cycle for subcooling under the practical working conditions (such as R744-PC-TCS). The greatest improvement of R744-PC-TCS can be achieved in the areas with poor climatic conditions, in which COP increases by 48.9% at an ambient temperature of 39 °C, and SEER increases by the maximum of 21.5% in hot summer and warm winter zones, compared with that of R744-TCS. Compared with R134a system, the R744-PC-TCS basically achieves the comparable or even higher energy efficiency. It can be concluded that the proposed R744-PC-TCS has a great potential to replace the existing R134a refrigeration system for the supermarket refrigeration application.